EXPLANATION OF THE ENTREPRENEURSHIP SOUL TO YOUTH, AL AMIN MOSQUE, PERUM GRIYA SURABAYA ASRI, SUMBEREJO, PAKAL CITY OF SURABAYA - Yanis Ulul Azmi; Pratiwi Dwi Karjati; Siti Asiah Murni (Journal of Community Service and Engagement, 2022)
Youthful entrepreneurship education is very much needed in this era. It is intended that children can have an entrepreneurial spirit, independence, and practice responsibility from an early age. Entrepreneurship education is usually given to subjects at school, however, here we want to instill the entrepreneurial spirit in mosque youth. A modern and educated society should not only be able to find work, but we should be able to create our own jobs and become entrepreneurs. Entrepreneurship can benefit yourself as well as others. It is hoped that the formation of an entrepreneurial spirit will be able to become a milestone for community change for the better. In this program we involve the youth of the Al Amin mosque. In addition to training children to be active, participatory, creative and innovative teenagers. Through this program, we hope that young people will also be able to be responsible and live independently.